2015
DOI: 10.1097/mib.0000000000000402
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Insult Impairs Lymph Flow, Increases Cellular Content of the Lymph, Alters Local Lymphatic Microenvironment, and Leads to Sustained Inflammation in the Rat Ileum

Abstract: Background Lymphatic dysfunction has been linked to inflammation since the 1930’s. Lymphatic function in the gut and mesentery is grossly underexplored in models of IBD despite the use of lymphatic occlusion in early models of IBD. Activation of the innate and adaptive immune system is a hallmark of TNBS-induced inflammation and is linked to disruption of the intrinsic lymph pump. Recent identification of crosstalk between lymphatic vessel resident immune cells and regulation of lymphatic vessel contractility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 83 publications
3
39
0
Order By: Relevance
“…Although the PCR experiments on intact lymphatics do not permit us to determine in which cell type the iNOS upregulation occurred, we observed that both lymphatic endothelial and muscle cells in culture exhibited upregulated iNOS mRNA expression following TNF-α treatment (Rehal, Roizes & von der Weid, unpublished data) and we can reasonably infer that both cell types are sensitive to TNF-α and contribute to lymphatic contractile dysfunction by upregulating iNOS expression and NO production. This proposal is further supported by other studies demonstrating iNOS upregulation in cultured lymphatic endothelial cells isolated from sheep, mouse and rat mesenteric lymphatic vessels upon stimulation with LPS, TNF-α, and other cytokines [17,42,45] and in mesenteric lymphatic vessels from old rats, which display an inflamed phenotype[51] Alternatively, NO could also be generated by immune cells reminiscent of macrophages that have recently been reported to populate the wall of mesenteric lymphatic vessels [12,16,40]. Indeed, some of these cells display NF-κB activation (see arrowheads in Fig.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Although the PCR experiments on intact lymphatics do not permit us to determine in which cell type the iNOS upregulation occurred, we observed that both lymphatic endothelial and muscle cells in culture exhibited upregulated iNOS mRNA expression following TNF-α treatment (Rehal, Roizes & von der Weid, unpublished data) and we can reasonably infer that both cell types are sensitive to TNF-α and contribute to lymphatic contractile dysfunction by upregulating iNOS expression and NO production. This proposal is further supported by other studies demonstrating iNOS upregulation in cultured lymphatic endothelial cells isolated from sheep, mouse and rat mesenteric lymphatic vessels upon stimulation with LPS, TNF-α, and other cytokines [17,42,45] and in mesenteric lymphatic vessels from old rats, which display an inflamed phenotype[51] Alternatively, NO could also be generated by immune cells reminiscent of macrophages that have recently been reported to populate the wall of mesenteric lymphatic vessels [12,16,40]. Indeed, some of these cells display NF-κB activation (see arrowheads in Fig.…”
Section: Discussionmentioning
confidence: 59%
“…However in these conditions, as demonstrated in rodent models of TNBS-induced ileitis [49,77], the ability of the mesenteric lymphatics to pump and thus promote intestinal lymph drainage is compromised. The findings presented here suggest that part of this dysfunction might be due to TNF-α, one of the pro-inflammatory cytokines upregulated in the ileum during TNBS-induced inflammation [16,64]. Indeed, we found that mRNA expressions of TNF-α and the TNF-α receptor TNFR1 were significantly upregulated in lymphatic vessels following TNBS-induced ileitis, suggesting that the inflammation spread to the mesentery and that the lymphatic vessels were indeed inflamed.…”
Section: Discussionmentioning
confidence: 68%
“…121,122 In rat and guinea pig models of intestinal inflammation, indeed, the contractile capacity within isolated collecting mesenteric lymphatics is compromised, and this effect correlates with lymphatic dysfunction, lymphatic vessel dilation and mucosal inflammation. 88,103,123,124 Furthermore, these studies have shown cyclooxygenase (cyclooxygenase 1/2) or inducible nitric oxide synthase inhibitors improve lymphatic pumping in non-contracting lymphatics in experimental IBD, suggesting prostanoids and nitric oxide released during intestinal inflammation contribute to diminished lymphatic contractile activity.…”
Section: Roles Of Lymphatics In Inflammationmentioning
confidence: 99%
“…Lymph flow increases in acute inflammation, but reductions in lymph transport during chronic inflammation have also been reported. 91,[101][102][103] Lymph flow increases within minutes of acute intestinal inflammation and under acute edemagenic stress (i.e. infusion of isotonic saline).…”
Section: Roles Of Lymphatics In Inflammationmentioning
confidence: 99%
See 1 more Smart Citation